Peran Regulasi Emosi dan Harga Diri dalam Keberlanjutan Ibu Menyusui - Dina Aprilia; Nur Alam Fajar; Elvi Sunarsih (LPPM Institut Pendidikan Nusantara Global, 2025)
Breastfeeding continuation in Indonesia still faces complex challenges despite scientifically proven optimal benefits of breast milk, where psychological factors particularly emotional regulation and maternal self-esteem are often overlooked in interventions to improve breastfeeding success. This study aims to analyze the role of emotional regulation and self-esteem on breastfeeding continuation and explore the interaction of these two psychological constructs in influencing breastfeeding duration. The study employs a narrative literature review approach with systematic literature search on electronic databases including PubMed, Google Scholar, PsycINFO, and Scopus for the period 2020-2025, where data analysis was conducted thematically with narrative synthesis to integrate findings from various studies. The results indicate that adaptive emotional regulation facilitates mothers' ability to manage psychological distress that can disrupt the physiological mechanisms of lactation, while high self-esteem forms the foundation for developing breastfeeding self-efficacy which predicts longer breastfeeding duration. The synergistic interaction of both constructs creates protective mechanisms against premature breastfeeding cessation, where breastfeeding intention formed since antenatal period becomes the most reliable predictor of actual breastfeeding behavior. This study concludes that maternal emotional regulation and self-esteem contribute significantly to breastfeeding continuation through complex interacting psychobiological mechanisms, indicating the need for comprehensive psychosocial interventions from the antenatal period to increase breastfeeding success rates in indonesia.